Association Between Dietary Patterns and Kidney Function in Patients With Chronic Kidney Disease: A Cross-Sectional Analysis of the German Chronic Kidney Disease Study - Heindel, Judith; Baid-Agrawal, Seema; Rebholz, Casey M.; Nadal, Jennifer; Schmid, Matthias; Schaeffner, Elke; Schneider, Markus; Meiselbach, Heike; Kaesler, Nadine; Bergmann, Manuela; Ernst, Sabine; Krane, Vera; et al. (Journal of Renal Nutrition, 2019)
Objective: In the general population, “healthy” dietary patterns are associated with improved health outcomes, but data on associations between observance of specific dietary patterns and kidney function in patients with chronic kidney disease (CKD) are sparse. Methods: Dietary intake was evaluated using food frequency questionnaires in patients with moderately severe CKD under nephrology care enrolled into the observational multicenter German CKD study. The Dietary Approaches to Stop Hypertension (DASH) diet score, Mediterranean diet score, and German Food Pyramid Index (GFPI) were calculated and their association with estimated glomerular filtration rate (eGFR) and albuminuria was assessed by multivariable linear regression analysis, adjusted for gender, age, body mass index, energy intake, smoking status, alcohol intake, education, high-density lipoprotein-cholesterol (HDL- cholesterol), low-density lipoprotein-cholesterol (LDL-cholesterol), hypertension, and diabetes mellitus. Results: A total of 2,813 patients (41% women; age 60.1 ± 11.6 years) were included in the analysis. High DASH diet score and GFPI were associated with lower systolic blood pressure and lower intake of antihypertensive medication, higher HDL, and lower uric acid levels. Mediterranean-style diet was associated with lower prevalence of diabetes mellitus. Higher DASH and Mediterranean diet scores were associated with higher eGFR (β-coefficient = 1.226, P <.001; β-coefficient = 0.932, P =.007, respectively). In contrast, GFPI was not associated with eGFR. For the individual components of the dietary patterns, higher intake of nuts and legumes, cereals, fish, and polyunsaturated fats was associated with higher eGFR and higher intake of dairy, composed of low- and whole-fat dairy, was associated with lower eGFR. No association was found between dietary patterns and albuminuria. Conclusion: Higher observance of the DASH or Mediterranean diet, but not German food pyramid recommendations, was associated with higher eGFR among patients with CKD. Improving dietary habits may offer an opportunity to better control comorbidities and kidney function decline in patients with CKD.
CRIS-Team Scopus Importer:2019-12-27